SISTEMA DE GESTIÓN DE INVENTARIOS PARA COMPAÑÍAS DE HARDWARE - CASO DE ESTUDIO - Ana Maria Rodriguez; Tania Sabogal Cáceres; Ever Fuentes Rojas (Revista Ingeniería, Matemáticas y Ciencias de la Información)
Some hardware assembly and marketing companies do not apply proper inventory management, causing failures in theproduct records, which can lead to shortages if there is an unexpected high demand, affecting the costs of ledgers andgenerating the need for an inventory management system. For this purpose, a methodological process was carried out,starting with the diagnosis, identifying the main factors that need to be improved concerning the management ofmerchandise, such as lack of inventory policies or reorder level, found through tools such as the SWOT, IshikawaDiagram and Vester Matrix. Subsequently, an ABC classification was made, in which 1664 products are ordered and 118of them belong to category A and applying goodness-of-fit tests. Then, the system is characterized and the mathematicalmodels that adjust to the proposed conditions are selected: CEP without shortages and discount by suppliers, which isvalidated with a simulation. As a result of this process, the policy is established and a 95% improvement in the informationquality is observed as a result. Variables part of the models are proposed and developed in the simulation and improvethe system by 20% because they impact several products which are the most essential for the company.